IMPACT OF MULTIDISCIPLINARY CARE IN GYNECOLOGICAL CANCER PATIENTS: Multidisciplinary Care in Gynecological Cancer Patients - Tabassum, Arfa; Mahmud, Ghazala; Tasnim, Nasira; Bangash, Kausar Tasneem; Malik, Sumera (Pakistan Armed Forces Medical Journal, 2016)
Objective: To determine the impact of multidisciplinary care in Gynecological cancer patients through multidisciplinary meetings (MDM) at MCH centre, Pakistan Institute of Medical Sciences (PIMS), Islamabad.Study Design: A pre and post intervention comparative study.Place and Duration of Study: The study was conducted at MCH centre, PIMS and Nuclear Oncology and Radiotherapy Institute, Islamabad from 1st April 2009 to 31st Mar 2010.Material and Methods: MDM is a regularly scheduled meeting of core and limited team members for the purpose of prospective treatment and care planning of newly diagnosed cancer patients. It was started in 2009 in order to improve the management of the cancer patients according to the international recommendations. In a total of 1 year study period 24 meetings were held. The major audit tool was the documentation of the meeting and its outcomes, patient communication and record of the Nuclear Oncology and Radiotherapy Institute of Islamabad (NORI). A postgraduate student was deputed for documentation.Results: The study identified that MDM helped in achieving many of the best practices of international recommendations which include team approach to treatment planning as well as to care provision, throughout the complete patient pathway. The workload almost doubled as regards the surgery and outdoor cancer claims. There was a shorter delay to first seen in the cancer clinic and shorter duration from diagnosis to treatment. Team members were present in 90-100% of the meetings.Conclusion: MDM has swiftly improved the quality of care and follow up of patients with gynecological cancers and should be conducted at all tertiary care hospitals. Problems of access to high quality and timely care of poor patients in public sector should be addressed as poor patients are not compliant to timely followup.